1991
DOI: 10.1007/bf01883605
|View full text |Cite
|
Sign up to set email alerts
|

Gene-deletion and carrier detections, and prenatal diagnosis of Duchenne muscular dystrophy by analysis of the dystrophin gene amplified by polymerase chain reaction

Abstract: SummaryPolymerase chain reaction (PCR)-based diagnosis was carried out in 62 patients (57 probands) with Duchenne or Becket muscular dystrophy (DMD or BMD) and 226 members in 57 families. The PCR studies were also performed for carrier detection in 57 mothers and 58 sisters, and prenatal diagnosis of 4 fetuses at risk of DMD. The PCR with 7 sets of primers, which amplify 7 different exon-sequences of the dystrophin gene, detected gene deletion of at least one exon in 49 ~ of the probands. The PCR with the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The allele frequencies in the pERT87 locus detected with three combinations of primer and enzyme sets were well comparable to those previously reported for Japanese and Chinese females (Akita et al, 1987;Shimmoto et al, 1988;Sugino et aL, 1989;Fujishita et aL, 1991;Soong et aL, 1991). However, they were quite different from those in the Caucasian, Spanish, Indian and black populations (Kunkel et al, 1985(Kunkel et al, , 1986Lindlof et aL, 1987;Schwartz and Barjon, 1987;Roberts et al, 1989;Gokgoz et aI., 1993;A1-Maghtheh et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…The allele frequencies in the pERT87 locus detected with three combinations of primer and enzyme sets were well comparable to those previously reported for Japanese and Chinese females (Akita et al, 1987;Shimmoto et al, 1988;Sugino et aL, 1989;Fujishita et aL, 1991;Soong et aL, 1991). However, they were quite different from those in the Caucasian, Spanish, Indian and black populations (Kunkel et al, 1985(Kunkel et al, , 1986Lindlof et aL, 1987;Schwartz and Barjon, 1987;Roberts et al, 1989;Gokgoz et aI., 1993;A1-Maghtheh et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…This rate was increased to 98 ~ when the number of regions amplified was expanded to 19 exons (Beggs et al, 1990). Fujishita et aL (1991) reported that 26 (92~) of 28 deletions observed with Southern analysis were detected by PCR using only seven primer sets. Our study also showed a high detection rate that was almost consistent with these results.…”
Section: Discussionmentioning
confidence: 98%
“…The recombination rate is 4 %. Fujishita et al (1991) [24] reported that the recombination between pERT 87-8 locus (against cDNA 2b-3) and 3' end portion of the gene was found in 4 of 36 members in Japanese. and with a fraction of 11%.…”
Section: Methodsmentioning
confidence: 99%